Understanding How Project Complexity and Interoperability Standards Inϐluence the Effectiveness of Smart Construction Technologies - Josh Chew (Journal of ICT, Design, Engineering and Technological Science, 2026)
The growing use of smart construction technologies has made construction projects evolve into data‑driven engineering frame‑ works. Still, the level at which the technologies can optimize project integration performance is subject to the preconditions of the underlying systems. This paper formulates a system‑based computational model to analyze how the capability of smart construction technology can influence the project integration performance under the moderating influence of the project complexity and data interoperability standards. Based on the data obtained through the work with 233 professionals who dealt with digitally enabled construction projects in Singapore, the study conceptualizes construction projects as socio‑technical systems where digital technologies can be seen as subsystems of performance enhancement under different environmental limitations. They used a MATLAB‑based analytical framework to estimate the parameters of the system, the effect of interaction, and the predictive accuracy. The findings show that the capability of smart construction technology has a strong positive impact on project integration performance through enhancing the consistency of design‑data, cost alignment, and schedule coordination. This relationship was revealed to be undermined by project complexity due to the creation of system‑level disturbances, and data interoperability standards were found to be a strong force that could modify the effect of tech capability by improving the level of subsystem integration and the coherence of information. The high explanatory and predictive capability of the proposed model has validated that it is a strong model to use in evaluating engineering performance. This study contributes to the socio‑technical systems theory and offers quantitative data that the optimal integration performance is achieved when the deployment of digital capability is coordinated with good complexity management and a strong interoperability architecture. The results provide practical information to engineers, system designers, and policymakers who are interested in optimizing digitally integrated construction systems.